Biocompatible fluorocarbon liquid underlays for in situ extraction of isoprenoids from microbial cultures. Issue 26 (6th June 2022) - Overmans, Sebastian; Lauersen, Kyle J.
Abstract : A novel bioprocess to capture and purify terpenoids produced by engineered microbes using 2-phase cultivation of the algae with liquid perfluorocarbons followed by liquid–liquid extraction of the terpenoids with ethanol. Abstract : Microbial production of heterologous metabolites is now a mature technology in many host organisms, opening new avenues for green production processes of specialty chemicals. At lab scale, petroleum-based hydrophobic bio-compatible solvents like dodecane can be used as a second phase on top of microbial cultures to act as a physical sink for heterologous hydrocarbon products like isoprenoids. However, this approach has significant drawbacks at scale due to the difficulty of handling solvents and their potential contamination with unwanted byproducts of their manufacture. We discovered that synthetic perfluorocarbon liquids (FCs), commonly used for heat transfer, can also act as physical sinks for microbially produced isoprenoid compounds. FCs are stable, inert, and are amenable to direct liquid–liquid extraction with alcohols for rapid product isolation. These liquids are more dense than water and form a lower phase to microbial cultures rather than an upper phase as with other solvents. Their ability to form an under-layer or 'underlay' also enables the cultivation of microbes directly at the FC–culture medium interface via gravity settling, which could open their application for filamentous or mat-forming organisms. We present comparisons of the isoprenoid extraction potential of three commercial FCs: FC-3283, FC-40, and FC-770 with engineered green microalga cultures producing patchoulol, taxadiene, casbene, or 13 R (+) manoyl oxide. We demonstrate that FCs are promising alternatives to traditional solvents and open new avenues in bio-process design for microbial heterologous metabolite milking.